2018
DOI: 10.1186/s12903-018-0627-y
|View full text |Cite
|
Sign up to set email alerts
|

Can a brief psychological intervention improve oral health behaviour? A randomised controlled trial

Abstract: BackgroundDental caries is a major public health issue affecting a large proportion of the general population. The disease is associated with behavioural factors and is thus preventable to a high degree. Individuals may need assistance to be able to change their oral health behaviour. There is a lack of such interventions for adults affected by severe caries. The aim of the study was to evaluate the effect of Acceptance and Commitment Therapy (ACT), a form of cognitive behavioural therapy, on oral health behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…It is widely debated 1) the extent to which information giving alone leads to change (Yevlahova and Satur 2009), 2) if short-term knowledge gain translates into sustained oral health improvements (Baelum 2011), and 3) whether the message should be delivered by the dentist or another member of the team (Baelum 2011). However, the success of short-term behavioral interventions within the dental practice suggests that patients can be encouraged to change their behavior, leading to positive oral health outcomes with the correct support (Werner et al 2016; Wide et al 2018). Key to the sustainability of this long-term is the availability, skill set, and investment (valuing) of a dental team to provide such interventions in the practice without the external support from a research-led intervention.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely debated 1) the extent to which information giving alone leads to change (Yevlahova and Satur 2009), 2) if short-term knowledge gain translates into sustained oral health improvements (Baelum 2011), and 3) whether the message should be delivered by the dentist or another member of the team (Baelum 2011). However, the success of short-term behavioral interventions within the dental practice suggests that patients can be encouraged to change their behavior, leading to positive oral health outcomes with the correct support (Werner et al 2016; Wide et al 2018). Key to the sustainability of this long-term is the availability, skill set, and investment (valuing) of a dental team to provide such interventions in the practice without the external support from a research-led intervention.…”
Section: Discussionmentioning
confidence: 99%
“…ACT, with its psychological flexibility model, stresses the role of spirituality and mindfulness, and creates space for bringing positive experiential activities that carry a positive psychology perspective. ACT-based RCTs has shown that ACT to be effective to enhance work quality (Aasdahl et al, 2018;Finnes, Enebrink, Sampaio, Sorjonen, Dahl, Ghaderi, Nager, & Feldman, 2019), resilience (Bahreini & Sanagouye-Moharer, 2019), coaching (Levin, Haeger, & Cruz, 2019), marital relationship (Amidisimakani, Najarpourian, & Samavi, 2018), academic success (Paliliunas, Belisle, & Dixon, 2018), self-esteem (Rasooli & Kalantari, 2018), oral health (Wide, Hagman, Werner, & Hakeberg, 2018), mindfulness in sports (Dehghani, Saf, Vosoughi, Tebbenouri, & Zarnagh, 2018), parent training for parents who have a child with autism (Corti, Pergolizzi, Vanzin, Cargasacchi, Villa, Pozzi, & Molteni, 2018), positive parenting strategies (Moyer, Page, McMakin, Murrell, Lester, & Walker, 2018), mental health for college students (Grégoire, Lachance, Bouffard, & Dionne, 2018), and life-quality for people with HIV/AIDS (Faezipour, Ghanbaripanah, Seyedalinaghi, Hajiabdolbaghi, & Voltarelli, 2018), the elderly (Wicaksana, Wahju, Eko, & Yudara, 2018), and refugees (Tol et al, 2018). Similarly, ACT-based bibliotherapy RCTs have been reported to enhance mental health for staff and teachers (Jeffcoat & Hayes, 2012) and Japanese college students (Muto, Hayes, & Jeffcoat, 2011).…”
Section: Tanhan 200mentioning
confidence: 99%
“…ACT studies have been criticised especially for the choice of study design [ 15 ]. The present intervention has been evaluated in an RCT, showing high acceptability and positive effects on oral health behaviour [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we developed a two-session manual-based ACT behavioural intervention for young adult patients with dental caries. The intervention was evaluated in an RCT where positive effects on oral health behaviour were found, and significantly more in the ACT intervention group than in the control group [21]. The large majority of patients completed the study, which is promising with regard to treatment acceptability, as this age group is known for the highest therapy dropout rates [22].…”
Section: Introductionmentioning
confidence: 99%